FDI and manufacturing growth: Bound test and ARDL approach - Rahman, Saif ur; Abu Bakar, Nor'Aznin (IJRSS, 2019)
The objective of this study is to investigate the effect of foreign direct investment (FDI) toward manufacturing value added growth in the context of developing economies like Pakistan. The study used annual data for the period 1972-2017. By applying the cointegration method known as "bounds test" and the autoregressive distributed lag (ARDL) approach to find both long term and short-term effect of FDI on manufacturing value added growth. Meanwhile the foreign direct investment and exports has also shown a significant impact on MAU in long run and short run. In addition, long run estimates show that foreign direct investment, employment and exports positively influence the Pakistan‟s manufacturing value added growth, while market size also significantly affect with negative sign of coefficient value and the employment insignificantly affect with positive sign. Our results suggest that Pakistan should consider appropriate positive policies regarding foreign direct investment, employment and exports to achieve high and stable manufacturing sector growth in the future. This paper contributes to the area of FDI and manufacturing sector growth by critically analyzing and synthesizing existing theory and research on FDI and manufacturing sector growth and with the help of advance technology and knowledge transfer